THE INFLUENCE OF COMPANY SIZE AND SOLVENCY ON INCOME WITH LENGTH OF BUSINESS AS A MEDIATION VARIABLE IN MANUFACTURING SECTOR COMPANIES ON THE INDONESIAN STOCK EXCHANGE IN 2018-2022: PENGARUH UKURAN PERUSAHAAN DAN SOLVABILITAS TERHADAP PENDAPATAN DENGAN LAMA USAHA SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN SEKTOR MANUFAKTUR YANG ADA PADA BURSA EFEK INDONESIA TAHUN 2018-2022 - Gulo, Otonius; Ndruru, Desman (LPPM UPMI, 2023)
The aim of this research is to analyze the direct and indirect influence of company size quality and solvency on length of business partially or simultaneously, to analyze the direct and indirect influence of company size and solvency on revenue partially or simultaneously. This type of causal associative quantitative research, the population used on the Indonesian Stock Exchange in 2018-2022, while the number of samples used in the research was 10 companies. The test tool used is path analysis with SPSS program application tools. The results of this study show that company size has a positive influence on income of 46.6%, whereas by using the mediation variable length of business, company size has no direct effect on income, Solvency has no direct effect on income, whereas by using the mediation variable length of business , solvency has no direct effect at 28%. Company size and solvency have a significant effect on income through the mediation of length of business, namely 48.1%, while the rest is influenced by other variables outside the model.